ANALYZING THE NEXUS OF POLITICAL AUTOCRACY, ECONOMIC STRAIN, AND HUMAN RIGHTS VIOLATIONS IN UGANDA - Mwambembe, Herbert Nathan; Asad, Shibli Jamal Shariff (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
The political situation in Uganda is heavily influenced by a history of civil wars, political unrest, and ethnic fractionalization (Rohner et al., 2011; Bananuka et al., 2019; Bananuka et al., 2019). The dominance of certain ethnic groups in the army and political leadership has been a recurring theme, leading to power struggles and instability (Rohner et al., 2011). The country gained independence in 1962, but soon after, it faced civil wars and political turmoil (Bananuka et al., 2019; Bananuka et al., 2019). The political settlement, or the basic political bargain among powerful actors, deeply affects the delivery of public services, including health care (Croke, 2023). The influence of ethnicity on political power and the potential for conflict is a significant concern in Uganda (Tripp, 1994; Meyerson, 2022). Moreover, the country's political climate has been characterized by quasi-authoritarian rule, which has influenced corruption and anti-corruption efforts (Tangri Mwenda, 2006; Peiffer et al., 2021).